Bioinspired Bare Bones Mayfly Algorithm for Large-Scale Spherical Minimum Spanning Tree - Zhang, Tian; Zhou, Yongquan; Zhou, Guo; Deng, Wu; Luo, Qifang (Frontiers in Bioengineering and Biotechnology, 2022)
Mayfly algorithm (MA) is a bio-inspired algorithm based on population proposed in recent years and has been successfully applied to many engineering problems. However, it has too many parameters, which makes it difficult to set and adjust a set of appropriate parameters for different problems. To avoid parameter adjustment, a bio-inspired bare bones mayfly algorithm (BBMA) is proposed. The BBMA uses Gaussian distribution and Lévy flight, improves the convergence speed and solution accuracy, balance the exploration and exploitation of the algorithm. The minimum spanning tree (MST) problem is a classic combinatorial optimization problem. This paper gives a mathematical model for solving a variant of the MST problem in which all points and solution are on a sphere. Finally, the BBMA is used to solve the large-scale spherical MST problem, and the results are compared and analyzed with other well-known algorithms. Experimental results show that the proposed algorithm has better performance than other algorithms in solving spherical MST problem.